GREEN FINANCING AND POLICY SUPPORT FOR SUSTAINABLE TOURISM INITIATIVES IN NIGERIA - Bello, Lateefat Adeola; Okeke, Clementina Chika (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
Sustainable tourism plays a vital role in addressing pressing global challenges such as climate change, biodiversity loss, and economic instability. This paper explores the importance of green financing and supportive policies in fostering sustainable tourism initiatives. It highlights mechanisms like green bonds, biodiversity-focused investments, and policy incentives that are instrumental in minimising the ecological footprint of tourism while simultaneously generating economic advantages. The research identifies key challenges faced by the sector, including limited access to financing, inconsistencies in regulatory frameworks, and gaps in technical expertise. The paper proposes strategic solutions to address these issues that foster collaboration among various stakeholders, including governments, financial institutions, and local communities. The study focuses on how financial strategies can turn tourism obstacles into opportunities for environmental and social advancement. It emphasises the need for eco-friendly tourism practices that not only yield profits but also deliver social benefits. By assessing funding mechanisms and policy frameworks that engage diverse stakeholders, the research aims to promote authentic sustainability. The investigation reveals that innovative financing and supportive policies can enhance sustainable development initiatives by addressing both environmental and social dimensions. However, it also underscores challenges such as policy fragmentation and the risk of "greenwashing." The paper advocates for synchronised global policies and active local engagement to overcome these hurdles. Ultimately, it suggests actionable recommendations for enhancing green financing and adaptive policies that facilitate collaboration among all parties involved. This cohesive approach aims to transition the tourism sector from merely sustainable to regenerative, fostering ecosystem vitality and community development. The proposed model is adaptable across various industries striving for economic growth alongside environmental sustainability.